2017
DOI: 10.1136/tobaccocontrol-2017-053795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health-oriented descriptors on combustible cigarette and electronic cigarette packaging: an experiment among adult smokers in the United States

Abstract: The effect of health-oriented language was significant for combustible cigarettesand e-cigarette packages. Policies to restrict health-oriented language on cigarette and e-cigarette packaging are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…References such as ‘natural’ and ‘organic’ are among the most common health‐oriented descriptors for consumable tobacco products, and have been shown to increase the appeal of food and tobacco products [19,51–53]. In the present study, products labelled as organic/natural were perceived as ‘less harmful’…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…References such as ‘natural’ and ‘organic’ are among the most common health‐oriented descriptors for consumable tobacco products, and have been shown to increase the appeal of food and tobacco products [19,51–53]. In the present study, products labelled as organic/natural were perceived as ‘less harmful’…”
Section: Discussionmentioning
confidence: 68%
“…For example, lighter colours communicate cues that elicit perceptions of reduced harm and strength, superior quality and better brand recognition [14][15][16][17][18]. Health-oriented descriptors have been shown to increase intentions to purchase, increase generally favourable perceptions and reduce perceived harm associated with the product's use [19]. Products presented in slim and thin designs increase attractiveness (particularly among women), communicate milder content and are perceived as less harmful [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Such an explanation is, of course, speculative. Another possible explanation is that the explicit messages contained what participants perceived as stronger arguments about vaping, and that such arguments suppressed smoking urge (Sanders-Jackson, Schleicher, Fortmann, & Henriksen, 2015;Sanders-Jackson, Tan, & Yie, 2018). This is also plausible given that stronger arguments are more likely to have impact in the context of anti-smoking messages (Lee, Cappella, Lerman, & Strasser, 2011;Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental studies have established that "organic" or "additive-free" descriptors decrease tobacco harm perceptions. [1][2][3][4][5] Two nationally representative studies have shown that Natural American Spirit (NAS) smokers specifically misunderstand the relative harm of their brand, which uses the "organic" descriptor on some products and, until late 2017, used the "additive-free" descriptor on its cigarette sub-brands. 6,7 However, the overall prevalence of belief that "organic" and "additive-free" tobacco products are less harmful than regular tobacco products has not been reported in the United States.…”
Section: Introductionmentioning
confidence: 99%